Fructooligosaccharides production from agro-wastes as alternative low-cost source - de la Rosa, Orlando (2019)
Background The prebiotic properties of fructooligosaccharides (FOS) are well documented. The high demand of functional food by the food, pharmaceutical and biotechnology industries have lead researchers to explore new and more feasible processes to produce FOS. Not only economical substrates are being exploited to reduce costs, but also, seeking to attend a global problem, the excessive generation of agro-industrial wastes that are polluting the earth, which are not being completely exploited, have been a concern. Scope and approach The purpose of this review is to present a concise (but wide-ranging) appraisal on the latest advances in fructooligosaccharides production from agro-wastes, as alternative low-cost source. Emphasis is placed on the examination, analysis and discussion of the prospects for using different agro-industrial waste bioresources for the production of FOS and FOS-producing enzymes. Key findings and conclusions The food, agro-industrial and forestry industries generate large volumes of waste, that are mainly composed of complex carbohydrates and crude proteins, that can be useful as nutrients for microbial growth, and enzymes or other metabolites production. Agro-industrial wastes are discarded, and its accumulation generates a severe environmental impact. The development of value-added processes using agro-industrial wastes is very attractive and becomes an environmentally friendly waste management method.